4.2-0.6x=3.6x 5x+2x=33.6 7x-4x=0.75 2x+7x+2.1=12 56x-32x-119=361 x+5=2x 3x+9=6x 4x-28=2x 2x+18=7x 5x=25*4-15x 7x-x+2*3=29.4 (28.8+5.5x+3.2)除2=71

来源:学生作业帮助网 编辑:作业帮 时间:2022/10/07 04:56:44
4.2-0.6x=3.6x 5x+2x=33.6 7x-4x=0.75 2x+7x+2.1=12 56x-32x-119=361 x+5=2x 3x+9=6x 4x-28=2x 2x+18=7x 5x=25*4-15x 7x-x+2*3=29.4 (28.8+5.5x+3.2)除2=71

4.2-0.6x=3.6x 5x+2x=33.6 7x-4x=0.75 2x+7x+2.1=12 56x-32x-119=361 x+5=2x 3x+9=6x 4x-28=2x 2x+18=7x 5x=25*4-15x 7x-x+2*3=29.4 (28.8+5.5x+3.2)除2=71
4.2-0.6x=3.6x 5x+2x=33.6 7x-4x=0.75 2x+7x+2.1=12 56x-32x-119=361 x+5=2x 3x+9=6x 4x-28=2x 2x+18=7x 5x=25*4-15x 7x-x+2*3=29.4 (28.8+5.5x+3.2)除2=71

4.2-0.6x=3.6x 5x+2x=33.6 7x-4x=0.75 2x+7x+2.1=12 56x-32x-119=361 x+5=2x 3x+9=6x 4x-28=2x 2x+18=7x 5x=25*4-15x 7x-x+2*3=29.4 (28.8+5.5x+3.2)除2=71
4.2-0.6x=3.6x
4.2=4.2x
x=1
5x+2x=33.6
7x=33.6
x=4.8
7x-4x=0.75
3x=0.75
x=0.25
2x+7x+2.1=12
9x=14.1
x=14.1\9
56x-32x-119=361
24x=480
x=20
x+5=2x
5=x
4x-28=2x
2x=28
x=14
2x+18=7x
18=5x
x=8\5
5x=25*4-15x
20x=100
x=5
7x-x+2*3=29.4
6x+6=29.4
6x=23.4
x=23.4\6
(28.8+5.5x+3.2)除2=71
14.4+2.25x+1.6=71
2.25x=55
x=55\2.25

(1)x=1 (2)x=4.8 (3)x=0.25 (4)x=1.1 (5) x=20 (6)x=5 (7)x=3 (8)x=14 (9)x=3.6 (10)x=5 (11)x=-4/6 (12)x=20